# How do you solve #x^2 + 3x + 6 = 0# by quadratic formula?

##### 2 Answers

#### Answer:

Substitute the coefficients

#x=(-3+-i sqrt(15))/2#

#### Explanation:

First note that the discriminant

#Delta = b^2-4ac = 3^2-(4xx1xx6) = 9 - 24 = -15#

So our quadratic equation has two Complex roots.

The roots are given by the quadratic formula:

#x = (-b+-sqrt(b^2-4ac))/(2a)#

#= (-b+-sqrt(Delta))/(2a)#

#=(-3+-sqrt(-15))/2#

#=(-3+-i sqrt(15))/2#

#### Answer:

The solutions are:

#### Explanation:

The equation is of the form

The **Discriminant** is given by:

As **NO REAL SOLUTIONS**

The solutions are found using the formula:

The solutions are: